Three‐dimensional modelling of computed tomography images of limb bones in gazelles (Gazella subgutturosa). (21st April 2020) - Demircioglu, Ismail; Gezer Ince, Nazan
Abstract: The objective of the present study was to model in 3D the detailed morphometric features of the thoracic and pelvic limb bones of the gazelle ( Gazella subgutturosa ), whose natural habitat is only in the Sanliurfa province, by using multidetector computerized tomography (MDCT) images. Materials from 14 (7 male and 7 female) dead gazelles were collected from the Harran University Veterinary Medicine Faculty clinics during or after treatment. MDCT images of the gazelles were taken and saved as DICOM (Digital Imaging and Communications in Medicine) files. MIMICS 20.1 software was used to generate a 3D reconstruction of the data, and morphological and morphometrical evaluation was performed. In respect of morphological features, the combined metacarpus (Mc) III and metacarpus Mc IV were the main weight‐bearing metacarpal bone, while Mc II and Mc V were rudimentary. On the femur, the lateral condyle was bigger than the medial condyle at the caudodistal end and the medial wing of the trochlea femoris was larger than the lateral. As with the thoracic limb, the combined metatarsus (Mt) III and metatarsus Mt IV were the main weight‐bearing metacarpal bone and they displayed a synostosis structure. There was no secondary metatarsus in the gazelles' pelvic limb. Based on digital measurements, the tibia was the longest bone of the gazelles' skeletal system, and there was a statistically significant sexual dimorphism throughout the skeleton at the levels of p < .05, p < .01 and p < .001. As a result, the present study's findings are useful as reference data for further studies on anatomy, surgery and archaezoology, while also being useful for classifying species and for forensic sciences.